2017
DOI: 10.1038/s41598-017-17941-7
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Platform for the Rapid Development of Antimicrobials

Abstract: Recent infectious outbreaks highlight the need for platform technologies that can be quickly deployed to develop therapeutics needed to contain the outbreak. We present a simple concept for rapid development of new antimicrobials. The goal was to produce in as little as one week thousands of doses of an intervention for a new pathogen. We tested the feasibility of a system based on antimicrobial synbodies. The system involves creating an array of 100 peptides that have been selected for broad capability to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Since these peptides are often very small and lack long-distance contacts that enforce specific 3D conformations, we wanted to explore how our models perform on these small structures. We compared the end-to-end distance of 3 hemagglutinin binding peptides 62 simulated in our ANM model, the ANMT model, and another popular coarse-grained protein model, AWSEM-MD. 37 Fig.…”
Section: Peptidesmentioning
confidence: 99%
“…Since these peptides are often very small and lack long-distance contacts that enforce specific 3D conformations, we wanted to explore how our models perform on these small structures. We compared the end-to-end distance of 3 hemagglutinin binding peptides 62 simulated in our ANM model, the ANMT model, and another popular coarse-grained protein model, AWSEM-MD. 37 Fig.…”
Section: Peptidesmentioning
confidence: 99%
“…Also important to this method’s success, the peptide libraries are random sequences, enabling screening and discovery of new, atypical, or novel cellular interactions with unique mechanisms of action. Third, the diverse phenotypic screening approach is adaptable for different microorganisms. ,, Finally, the large number of replicate microarrays produced with the photolithographic synthetic approach empowers experimental screening designs with large numbers of replicates or screening conditions. These important features and flexibility enable the design of screens that produce viable hits, even for challenging organisms, such as Mabs .…”
Section: Discussionmentioning
confidence: 99%
“…Peptides are 17-mers and are synthesized from 15 different amino acids, including d -versions of Lys, Arg, Ala, Leu, and Trp. Previously, we developed an AMP discovery method using spotted peptide microarrays of 10,000 peptides to identify peptides that bind to targeted bacteria. In this study, a 125,000 HD peptide microarray was used to screen for peptides with in vitro binding activity against Mabs S and R morphotypes. We then evaluated the activity of candidate peptides using a series of microdilution antimicrobial susceptibility assays performed in three culture media with and without a chelating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Betanzos et al, 2009 using luminescent LPS-quantum dots from O111:B4 and O55:B5 serotypes of E. coli revealed that peptides binding to E.coli LPS were highly enriched in aromatic and cationic amino acids and most inhibited growth [51]. Johnston et al, 2017 screened a range of pathogens (10 viruses and 11 bacteria) against a library of 10,000 peptides to identify shared and specific pathogen binding peptides that were used for the development of a pathogen binding 100-peptide microarray [52].…”
Section: Plos Onementioning
confidence: 99%